2016
DOI: 10.1158/1535-7163.mct-15-0093
|View full text |Cite
|
Sign up to set email alerts
|

ABCG2 and ABCB1 Limit the Efficacy of Dasatinib in a PDGF-B–Driven Brainstem Glioma Model

Abstract: Dasatinib is a multi-kinase inhibitor in clinical trials for glioma, and thus far failed to demonstrate significant efficacy. We investigated whether the ABC efflux transporters, ABCG2 and ABCB1, expressed in the blood-brain barrier (BBB), are limiting the efficacy of dasatinib in the treatment of glioma using genetic and pharmacological approaches. We utilized a genetic brainstem glioma mouse model driven by platelet-derived growth factor-B and p53 loss using abcg2/abcb1 wild type (ABC WT) or abcg2/abcb1 knoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 51 publications
3
44
0
Order By: Relevance
“…Pharmacokinetic studies revealed successful delivery of panobinostat into brain tissue of mice bearing genetically engineered BSG, providing evidence that it is able to reach potentially active concentrations in tumor tissue in this model. Furthermore, the distribution of panobinostat was higher in these brainstem tumors as compared to the normal cerebral cortical tissue, likely due to a compromised structural integrity of the BBB, which has been previously demonstrated in our GEMM [25], thus allowing a greater concentration of panobinostat to penetrate, and potentially treat, the tumor. Whether panobinostat reached potentially active levels in the HSJD-DIPG-007 xenograft model was not addressed here.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Pharmacokinetic studies revealed successful delivery of panobinostat into brain tissue of mice bearing genetically engineered BSG, providing evidence that it is able to reach potentially active concentrations in tumor tissue in this model. Furthermore, the distribution of panobinostat was higher in these brainstem tumors as compared to the normal cerebral cortical tissue, likely due to a compromised structural integrity of the BBB, which has been previously demonstrated in our GEMM [25], thus allowing a greater concentration of panobinostat to penetrate, and potentially treat, the tumor. Whether panobinostat reached potentially active levels in the HSJD-DIPG-007 xenograft model was not addressed here.…”
Section: Discussionmentioning
confidence: 59%
“…The lack of efficacy of systemic chemotherapy or targeted agents in DIPG has been partly attributed to their poor delivery into the tumor because of a relatively intact BBB, as evidenced by the minimal contrast enhancement in DIPGs with magnetic resonance imaging [3]. In fact, the BSG GEMM used here, although compromised relative to normal brain [25], exhibits reduced permeability as compared with tumors in the cerebral cortex [26]. One possible solution would be drug delivery via convection enhanced delivery (CED), a neurosurgical technique in which the drug is delivered through one to several catheters placed stereotactically directly within the tumor mass or around the tumor or resection cavity [27].…”
Section: Discussionmentioning
confidence: 99%
“…It is often assumed that the BBTB is completely disrupted; thus, its barrier function is often neglected during GBM drug design [329,330], but there are increasing clinical evidences showing that all the GBM present tumor zones with intact BBB, hindering drug permeability into the tumor (reviewed in [330]). This is supported by diverse murine studies showing a low drug penetration into tumors of xenografted mice [331][332][333] and PDGF-B-driven brainstem glioma models [334], due to ABC transporters P-gp and Bcrp [333,334]. In addition, a recent study using 3D-MSI showed a higher but non-homogeneous accumulation of erlotinib in the GBM tumors of xenografted mice than in brain parenchyma, proving that the BBTB is heterogeneously disrupted across the tumor [335].…”
Section: Multidrug Resistance In Glioma and The Blood-brain Tumor Barmentioning
confidence: 77%
“…The tumor microenvironment is a complex landscape of primary neoplastic cells and recruited supporting cells, including immune populations, fibroblasts, and vasculature. Cell signaling among these cells is complex and includes interactions through cytokines [266][267][268][269] , extracellular vesicles (reviewed in [270] ), and even the efflux of chemical signaling via ABC transporters [271,272] . The role of tumor immunosuppressive cells, such as tumor-associated macrophages [273][274][275] , regulatory T cells [276][277][278][279] , myeloid-derived suppressor cells [280][281][282] , continues to be evaluated in pediatric cancers, and these cells undoubtedly have roles in therapy resistance beyond immunotherapies.…”
Section: Future Areas Of Study In Pediatric Cancer Treatment Resistanmentioning
confidence: 99%